Soluble transferrin receptor levels in obese and non obese adolescents - Zul Febrianti; Fadil Oenzil; Firman Arbi; Gustina Lubis (Paediatrica Indonesiana, 2014)
Background Iron deficiency in children and adolescents maybe dueto an inadequate supply of iron as well as increased iron requirementsfor growth and developmental processes. The incr easing prevalence ofobesity puts children at risk of iron deficiency. Studies on the effectsof obesity on iron deficiency have focused on low grade systemicinflammation as well as examining soluble transferrin receptor levels(sTfR) as an indicator ofiron deficiency.Objective To compare sT fR levels in obese and non-obeseadolescents, assess for correlations between BMI, sTfR and obesity,and determine the risk of iron deficiency in obese adolescents .Method T his cross sectional study was conducted on 20 obeseand 20 non-obese adolescents aged 15-17 in East Aceh District,from September to December 20 11. Subject were chosen throughcluster sampling. The obese subjects had BMI > 95th percentileand the non-obese subjects had BMI s:851h percentile based onthe 2000 National Center for Health Statistics (NCHS). Exclusioncriteria were blood disorders, chronic diseases, and a history ofbleeding. Data were analyzed by Chi-square test and T test witha significance level of P < 0.05, and Pearson's correlation.Results The mean s TfR levels in obese adolescents was higher thanin non-obese adolescents, [2.59 (SD 0.76) vs 2.14 (SD 0.45) Î¼g/mL(P = 0.030)]. Iron deficiency (sTfR> 2.5 Î¼gimL) was more commonin obese than in non-obese adolescents [ (55% vs . 15%, respectively,(P = 0.019) ]. Analysis of the relationship between obesity accordingto BMI andsTfRrevealedan OR of 6.93; 95% CI 1.53 to3 1.38. Ther elationship between the BMI and sTfR levels indicated a positive,moderate strength of association (r = 0.392) .Conclusion The mean sT fR levels in obese adolescents is significantlyhigher than in non-obese individuals. Obese adolescentshave a 6.93 times higher risk of iron deficiency than non-obeseadolescents. Body mass index has a positive and moderate associationwith sTfR.